On symmetries of generalized Robertson-Walker spacetimes and applications. Issue 1 (2nd January 2017) - El-Sayied, H.K.; Shenawy, Sameh; Syied, Noha
ABSTRACT: The purpose of the present article is to study and characterize several types of symmetries of generalized Robertson-Walker spacetimes. Conformal vector fields, curvature and Ricci collineations are studied. Many implications for existence of these symmetries on generalized Robertson-Walker spacetimes are obtained. Finally, Ricci solitons on generalized Robertson-Walker spacetimes admitting conformal vector fields are investigated.